Anti-cancer effects of Kaempferia parviflora on ovarian cancer SKOV3 cells - Suthasinee Paramee; Siriwoot Sookkhee; Choompone Sakonwasun; Mingkwan Na Takuathung; Pitchaya Mungkornasawakul; Wutigri Nimlamool; Saranyapin Potikanond (BMC, 2018)
Abstract Background Kaempferia parviflora (KP) is an herb found in the north of Thailand and used as a folk medicine for improving vitality. Current reports have shown the anti-cancer activities of KP. However, the anti-cancer effects of KP on highly aggressive ovarian cancer have not been investigated. Therefore, we determined the effects of KP on cell proliferation, migration, and cell death in SKOV3 cells. Methods Ovarian cancer cell line, SKOV3 was used to investigate the anti-cancer effect of KP extract. Cell viability, cell proliferation, MMP activity, cell migration, and invasion were measured by MTT assay, cell counting, gelatin zymography, wound healing assay, and Transwell migration and invasion assays, respectively. Cell death was determined by trypan blue exclusion test, AnnexinV/PI with flow cytometry, and nuclear staining. The level of ERK and AKT phosphorylation, and caspase-3, caspase-7, caspase-9 was investigated by western blot analysis. Results KP extract was cytotoxic to SKOV3 cells when the concentration was increased, and this effect could still be observed even though EGF was present. Besides, the cell doubling time was significantly prolonged in the cells treated with KP. Moreover, KP strongly suppressed cell proliferation, cell migration and invasion. These consequences may be associated with the ability of KP in inhibiting the activity of MMP-2 and MMP-9 assayed by gelatin zymography. Moreover, KP at high concentrations could induce SKOV3 cell apoptosis demonstrated by AnnexinV/PI staining and flow cytometry. Consistently, nuclear labelling of cells treated with KP extract showed DNA fragmentation and deformity. The induction of caspase-3, caspase-7, and caspase-9 indicates that KP induces cell death through the intrinsic apoptotic pathway. The antitumor activities of KP might be regulated through PI3K/AKT and MAPK pathways since the phosphorylation of AKT and ERK1/2 was reduced. Conclusions The inhibitory effects of KP in cell proliferation, cell migration and invasion together with apoptotic cell death induction in SKOV3 cells suggest that KP has a potential to be a new candidate for ovarian cancer chemotherapeutic agent.